Effect of Salt and Storage Time on Physico-Chemical and Sensorial Properties of Beef Meatball - Tanny, RS; Hashem, MA; Akhter, S; Islam, MS; Azad, MAK; Ali, MS; Hossain, MM (Progressive Agriculture, 2014)
The experiment was conducted to find out the effect of salt and storage temperature on the physico-chemical properties of meatball. For this purpose meatball samples were divided into two parts; one is called fresh meatball and another is preserved meatball at different temperatures. Then the fresh samples as well as the preserved samples were divided into four subdivisions. Then these are treated with different salt levels (0, 1.5, 3 and 5% salt level).These Samples were stored at 4oC and -20oC temperature. Samples preserved at 4oC were stored in the refrigerator for 21 days and were analyzed on 7th day, 14th day and 21st day and samples preserved at -20oCwere stored in the refrigerator for 60 days and were analyzed on 15th day, 30th day, 45th day and 60thday. Dry matter content of all the samples increased with the advancement of storage time, temperature and salt concentration. Ash value decreased with the increase of storage time. Fat value of all the samples decreased with the advancement of salt concentration, storage time and temperature. pH value of all the samples decreased with the increasing of salt concentration, storage time and temperature. Cooking loss of all the samples increased with increasing of salt concentration but decreased with increasing of storage time and temperature. Dry matter in fresh sample were less than in preserved samples. CP % of fresh beef meatball was 22.31, 20.55, 14.55 and 20.13 at different salt concentration. The values of CP, DM, Ash and Fat also varied among the samples significantly (P<0.01). Beef meatball can be refrigerated for 60 days in different techniques with more or less difference in the quality. Highly significant differences are observed in preserved samples than in fresh samples at different salt levels. Fresh beef meatball treated with 1.5% salt found to be more acceptable in terms of sensory evaluation. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19117 Progress. Agric. 24(1&2): 137 - 147, 2013